2011
DOI: 10.1071/ch11278
|View full text |Cite
|
Sign up to set email alerts
|

Material design of ionic liquids to show temperature-sensitive LCST-type phase transition after mixing with water

Abstract: Phosphonium cations bearing different alkyl chains were coupled with several common anions so as to prepare ionic liquids (ILs) with diverse hydrophobicity. A temperature-driven phase behaviour of the mixture of various ILs and water has been examined. A few ILs were found to exhibit temperature-sensitive lower critical solution temperature (LCST)-type phase transition after mixing with water. The phase separation temperature (T c ) of the IL/water mixtures depended strongly on the hydrophobicity of the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 30 publications
6
93
0
1
Order By: Relevance
“…38 In agreement with the structural studies above mentioned, these unique features can be schematized according to Fig 6, being a consequence of ability of the well-defined structure of these ILs to be modified by incorporating the non-polar solute in specific regions that become expanded. ethylammonium hydrogen sulfate, ethylammonium formate, etc.)…”
Section: From Structure To Application As Sponge-like Ionic Liquidssupporting
confidence: 75%
“…38 In agreement with the structural studies above mentioned, these unique features can be schematized according to Fig 6, being a consequence of ability of the well-defined structure of these ILs to be modified by incorporating the non-polar solute in specific regions that become expanded. ethylammonium hydrogen sulfate, ethylammonium formate, etc.)…”
Section: From Structure To Application As Sponge-like Ionic Liquidssupporting
confidence: 75%
“…This circumvents the need for IL distillation completely and potentially offers considerable reduction in process energy costs. [19][20][21] Abe et al [22] have demonstrated the use of tetrabutylphosphonium hydroxide (60 wt %) for the dissolution of cellulose at room temperature. Recently, we submitted a patent application that describes this concept, [14] in which phosphonium-based ILs in combination with cosolvents allowed cellulose solubility.…”
Section: Introductionmentioning
confidence: 99%
“…7 The electric conductivity of the aqueous solution was measured using an electrical conduction metre with automatic temperature compensation (Hanna instruments, DiST4). It was prepared by direct neutralization of aqueous tetrabutylphosphonium hydroxide solutions with trifluoroacetic acid.…”
Section: Electric Conductivitymentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In particular, thermoresponsive phase behaviour of aqueous solutions of ILs has been extensively investigated in relation to phase transitions with lower critical solution temperatures (LCSTs) 6,12,13 as well as upper critical solution temperatures (UCSTs). 7 The chemical structure of [P 4444 ]CF 3 COO is shown in Fig. This transition is caused because the mixing entropic contribution in the mixing Gibbs energy generally becomes more dominant as the temperature (T) increases.…”
Section: Introductionmentioning
confidence: 99%